Applying Gravity Model to Analyze Determinants of International Migration from Developing Countries (Global Journal of Human-Social Science, 2020)
The rising numbers of immigrants from developing countries during the past decades is the most important economic issues facing the countries of the world Understanding the underlying motives behind the phenomenon of international migration is a prerequisite for making informed political decisions Therefore this study aims to investigate the determinants of individuals migration from low- and middleincome developing countries to high income countries Canada France Germany Britain USA using Unbalanced Panel Data For the period of 1995-2017 The study used the utility function through the push and pull factors of international migration by applying standard analysis to the extended gravity model for a number of developing countries using negative binomial regression this is considered as the most appropriate to estimate the relationship between the number of immigrants as a dependent variable and other explanatory variables in this study The results of the study showed that the level of per capita income is the most important economic determinant In ddition to the presence of former immigrants from the same immigrant country in the destination countries
Keywords: international migration; gravity model; developing countries; negative binomial